Estudo da degradação de petróleos ácidos por técnicas analíticas de alta resolução - Barros, Eliane Valéria de (2016)
In the refining process of petroleum the corrosion caused by naphthenic acids (NA) is one of the most aggressive,and it can be accentuated when in presence of other compounds usually found in oil. Herein, oils samples weresubjected to thermal degradation process aiming the understanding of its behavior at the molecular level and to evaluate its physicochemical properties as a function of degradation time. In the first part of this study, anacid oil sample was subjected tothermal degradation process at 350 °C. Additionally, the oil was characterized by classic and high resolution analytical techniques. The obtained results showed that the oil exposed to longer degradation times presented characteristics of “lighter” oil due to mainly disaggregation of resins and asphaltenes. Total Acid number (TAN) measurements displayed a decrease of 68.3% (from 2.0 to 0.75 mg KOH g-1) of its initial value after 36h of degradation at 350 oC. Other important changes observed included an increase in API gravity (of two decimal places from 17 to 19), and decreases in the pour point from -12 to -36 oC, in the kinematic viscosity in 86.5% and of total sulfur content in 5.2% (from 0.58 to 0.55 wt%). The HTGC and NMR results showed that the saturated fraction is not affected during the thermal stress process, whereas a subtle increase in the number of aromatic compounds was observed as a function of degradation time. This behavior can be attributed to the disaggregationof resins and asphaltenes as well as to the decarboxylation process that was confirmed by ESI(-)-FT-ICR MS, where a reduction of average mass molar distribution from 466 to 450 Da was observed.In the second part of the work, a second sample of oil was degraded at 320 ° C and characterized by ESI (--FT-ICR MS and 1H NMR. Different extraction methodologies were used to investigate the behavior of the acidic species present. Regarding the collective extractions of NAs, solid phase extraction (SPE) was more efficient in relation to liquid-liquid extraction. Since the results of ESI(-)-FT-ICR MS showed an increase in the amplitude of observation of the acidic compounds and a greater number of compounds of class O2, which corresponded to almost 100% of all the processing. The integrations of the 1H NMR spectra of the acid fractions as a function of the molecular weight (Mw) emphasized the expressive presence of alkyl compounds, which had already been observed in the first part of the work. The successive removals of the acids of smallercarbon chains which reduced the ionic suppression on the larger acid species. The MS results of the extracts as a function of Mwdid not show typical Gaussian spectra for the last fractions (degraded for 24 and 72 hours), suggesting that cracking reduced the number of acid species for times of major degradation. The DBE versus NC graphs of the extracts of all samples (original oil and degraded at 24 and 72 hours) showed that there is an increase in the number of cyclizations, which corroborated with the previous results regarding the increase of the aromatic content.The reduction of the resin and asphaltenes content due to the thermal degradationsuggestthe"transformation" of heavy oil into considered "lighter" oils.